2010
DOI: 10.1016/j.ijrobp.2009.02.024
|View full text |Cite
|
Sign up to set email alerts
|

Late Effects After Radiotherapy for Locally Advanced Cervical Cancer: Comparison of Two Brachytherapy Schedules and Effect of Dose Delivered Weekly

Abstract: To establish dose-response relationships for late complications, three-dimensional imaging and dose-volume histogram parameters are needed. We found some indications that 20 Gy/wk is an upper tolerance level when the dose to the International Commission on Radiation Units and Measurements rectum point is 81 Gy(alpha/beta=3) (isoeffective [equivalent] dose of 2-Gy fractions). However, additional investigations using three-dimensional data are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…However, it is well known that acute and late radiation morbidity may be correlated with each other [36], which argues against combining concomitant chemotherapy involving multiple drug regimens [37] with high-dose-rate brachytherapy or accelerated radiotherapy regimens requiring a high weekly cumulative dose [38,39]. Most institutions using HDR would therefore not give more than 2 BT fractions per week for a cumulative prescribed BT dose of 15-18 Gy (EQD2).…”
Section: Implant and Fractionation Strategies For Image-guided Bt In mentioning
confidence: 99%
“…However, it is well known that acute and late radiation morbidity may be correlated with each other [36], which argues against combining concomitant chemotherapy involving multiple drug regimens [37] with high-dose-rate brachytherapy or accelerated radiotherapy regimens requiring a high weekly cumulative dose [38,39]. Most institutions using HDR would therefore not give more than 2 BT fractions per week for a cumulative prescribed BT dose of 15-18 Gy (EQD2).…”
Section: Implant and Fractionation Strategies For Image-guided Bt In mentioning
confidence: 99%
“…Some studies attempting to shorten the OTT also reported increased complication rates . Erridge et al.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings support this hypothesis. Because radiotherapy for cervical cancer includes EBRT and ICBT, Some studies attempting to shorten the OTT also reported increased complication rates [17][18][19]. Erridge et al also noted that patients with the shortest OTT had an increased incidence of late morbidity without the involvement of cause-specific survival [20].…”
Section: Discussionmentioning
confidence: 99%
“…However, the dose distribution from RALS is highly inhomogeneous, and several different methods of specifying the dose constraints have been published. Moreover, the risk assessment is also complicated because the dose contribution from EBRT and RALS varies considerably from study to study [46, 78]. …”
Section: Discussionmentioning
confidence: 99%